Complete DNA sequences of the mitochondrial genomes of the pathogenic yeasts Candida orthopsilosis and Candida metapsilosis: Insight into the evolution of linear DNA genomes from mitochondrial telomere mutants. - WOLFE, KENNETH (Oxford University Press, 2006)
We determined complete mitochondrial DNA sequences of the two yeast species, Candida orthopsilosis and Candida metapsilosis, and compared them with the linear mitochondrial genome of their close relative, C.parapsilosis. Mitochondria of all the three species harbor compact genomes encoding the same set of genes arranged in the identical order. Differences in the length of these genomes result mainly from the presence/absence of introns. Multiple alterations were identified also in the sequences of the ribosomal and transfer RNAs, and proteins. However, the most striking feature of C.orthopsilosis and C.metapsilosis is the existence of strains differing in the molecular form of the mitochondrial genome (circular-mapping versus linear). Their analysis opens a unique window for understanding the role of mitochondrial telomeres in the stability and evolution of molecular architecture of the genome. Our results indicate that the circular-mapping mitochondrial genome derived from the linear form by intramolecular end-to-end fusions. Moreover, we suggest that the linear mitochondrial genome evolved from a circular-mapping form present in a common ancestor of the three species and, at the same time, the emergence of mitochondrial telomeres enabled the formation of linear monomeric DNA forms. In addition, comparison of isogenic C.metapsilosis strains differing in the form of the organellar genome suggests a possibility that, under some circumstances, the linearity and/or the presence of telomeres provide a competitive advantage over a circular-mapping mitochondrial genome.
PUBLISHED
Keywords: Genetics; Candida orthopsilosis; Candida metapsilosis